2010
DOI: 10.1186/1423-0127-17-s1-s20
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and skeletal muscle abnormality in taurine transporter-knockout mice

Abstract: Taurine, a sulfur-containing β-amino acid, is highly contained in heart and skeletal muscle. Taurine has a variety of biological actions, such as ion movement, calcium handling and cytoprotection in the cardiac and skeletal muscles. Meanwhile, taurine deficiency leads various pathologies, including dilated cardiomyopathy, in cat and fox. However, the essential role of taurine depletion on pathogenesis has not been fully clarified. To address the physiological role of taurine in mammalian tissues, taurine trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 26 publications
0
68
0
Order By: Relevance
“…considered to be present in skeletal muscles and kidneys (16), and it was suggested that taurine was produced elsewhere and transported to these tissues (21,22). In this study, the expression and biochemical activity of GADL1 in muscles suggested that muscle taurine might be produced in situ.…”
Section: Discussionmentioning
confidence: 58%
“…considered to be present in skeletal muscles and kidneys (16), and it was suggested that taurine was produced elsewhere and transported to these tissues (21,22). In this study, the expression and biochemical activity of GADL1 in muscles suggested that muscle taurine might be produced in situ.…”
Section: Discussionmentioning
confidence: 58%
“…org) and SMIT mRNA in the human skeletal muscle are low 16,17 and we could not detect the corresponding protein in normal muscle samples. However, TauT knockout mice suffer from muscle fiber atrophy and necrosis and reduced exercise endurance, 18,19 which implies that these factors could still be crucial factors for muscle recovery after damage. It has been observed that NFAT5 levels increase in the regenerating fibers of mouse tibial muscle following muscle tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of exon 1 of the TauT gene results in a striking (98%) decrease in heart and skeletal muscle taurine levels, with severely impaired skeletal muscle function and exercise capacity (Warskulat et al, 2004). TauT knockout mice also display severe abnormalities in muscle structure including decreased myofibre cross sectional area, myofilament fragmentation, and lipid droplets within the myofibre (Ito et al, 2008(Ito et al, , 2010.…”
Section: Introductionmentioning
confidence: 97%
“…1. Maintenance of the intracellular taurine pool depends on active uptake from the extracellular space by the high affinity, low capacity, Na + dependent transporter, TauT (Ito et al, 2010), and taurine is released from cells via volume insensitive and volume sensitive leak pathways (Lambert et al, 2014). The liver is responsible for export of a substantial proportion of the taurine body pool into the plasma, and absorption of taurine from the diet in the liver by hepatocytes requires TauT.…”
Section: Introductionmentioning
confidence: 99%